PENINGKATAN KUALITAS HIDUP LANSIA MELALUI AKTIVITAS PADUAN SUARA DI GEREJA - Ismudiati, Endang (PROMUSIKA, 2013)
The activity relationship between choir practicesand the improvement of elderly’s life quality expresses new understanding in art assessment. Musical experiences that has given a meaning in, and evoke the spirit of the elderly life, also contributes to their personal happiness. Choirs of the elderly that mostly found in Yogyakarta churches has generally contributed tothe elderly’s god quality of life. This study has been based on case study approach by applying Felce &Perry’s theory (1996) concerning the current quality of liferefers to the objective and subjective evaluation. The objective evaluation related to aspects of physical, material, social, and emotional while the subjective evaluation related to the personal satisfaction associated with the condition. This study concluded that choir activities done by the elderly can give positive contribution to the quality of life improvement. Based on thid finding, suggests that private as well as public institutions who carry out the elderly ctivities or nursing home to consider choir to be one of their service programs.Keywords: Choir, Quality of life, elderly